Susceptibility of clinical isolates of multiresistant Pseudomonas aeruginosa to a hospital disinfectant and molecular typing - Célia Maria Carvalho Pereira Araujo Romão; Yaisa Naziozeno de Faria; Luciana Roberto Pereira; Marise Dutra Asensi (Memorias do Instituto Oswaldo Cruz, 2005)
The aim of this study was to evaluate the susceptibility of 35 resistant Pseudomonas aeruginosa clinical isolates to a quaternary ammonium hospital disinfectant. The methodology was the AOAC Use-Dilution Test, with disinfectant at its use-concentration. In addition, the chromosomal DNA profile of the isolates were determined by macro-restriction pulsed field gel electrophoresis (PFGE) method aiming to verify the relatedness among them and the behavior of isolates from the same group regarding the susceptibility to the disinfectant. Seventy one percent of the isolates were multiresistant to antibiotics and 43% showed a reduced susceptibility to the disinfectant. The PFGE methodology detected 18 major clonal groups. We found isolates with reduced susceptibility to the disinfectant and we think that these are worrying data that should be further investigated including different organisms and chemical agents in order to demonstrate that microorganisms can be destroyed by biocide as necessary. We also found strains of the same clonal groups showing different susceptibility to the disinfectant. This is an interesting observation considering that only few works are available about this subject. PFGE profile seems not to be a reliable marker for resistance to disinfectants.